Efficacy of Remote Rehabilitation Combined with Outpatient Treatment in Mild Adolescent Idiopathic Scoliosis - DONG Jiaxing, WANG Liancheng, ZHANG Jinchai, WANG Shuai, ZHANG Yajie (Zhongguo quanke yixue, 2022)
Background Scoliosis is a common abnormal curvature of the spine. Patients with mild scoliosis are usually treated with outpatient physiotherapy, but satisfactory efficacy is associated with appropriate treatment time and frequency. The efficacy of offline physiotherapy may be affected by limited medical resources and patients' treatment time and geographical location. Remote rehabilitation may save patients' treatment time and increase the geographical accessibility of physiotherapy, making the therapy more simple and convenient. Objective To explore the efficacy of remote rehabilitation combined with outpatient treatment in mild adolescent idiopathic scoliosis (AIS) . Methods Fifty-eight eligible mild AIS patients were selected from Department of Rehabilitation Medicine, Tianjin Hospital from September 2020 to September 2021, and divided into three groups according to patients and their parents' selection of treatment: online group (n=18), combined group (n=20) and offline group (n=20). The online group received WeChat- and Tencent Video-based physiotherapeutic scoliosis specific exercise (PSSE), the combined group received both outpatient and WeChat- and Tencent Video-based PSSE treatment, and the offline group received outpatient PSSE treatment. Data of three groups were collected, including the main curve Cobb angle, coronal balance (CB), thoracic kyphosis (TK) angle, lumbar lordosis (LL) angle, sagittal vertical axis (SVA), angle of axial trunk rotation (ATR), parietal vertebra rotation (Raimondi), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), muscle activation rate (MAR) on both sides of paraspinal vertebrae, root mean square ratio (RMSR) of paraspinal muscles on both sides of paraspinal vertebrae, and the score of SRS-22 before and after treatment. Results The main curve Cobb angle, TK, SVA, ATR, Raimondi, SS, MAR on paraspinal vertebrae, RMSR on the concave side of the parietal vertebra and SRS-22 self-image and mental health domain scores were significantly different from those before treatment in all groups (P<0.05). Specifically, the combined group was superior to the other two groups in improved ATR and treatment satisfaction. The combined group had significantly improved main curve Cobb angle after treatment than the online group. The improvement of the concave MAR in either the combined group or offline group was significantly better than that in the online group (P<0.05) . Conclusion In mild AIS patients, remote rehabilitation combined with outpatient treatment could effectively slow down the progression of AIS curve, improve sagittal abnormality of spine, abnormal posture and vertebral rotation, increase the activation rate of paraspinal muscles on the concave side of paraspinal vertebra and improve the balance of paraspinal muscles on both sides of paraspinal vertebrae. Moreover, the combined therapy also improved the quality of life.